Penggunaan Instagram sebagai Media Dakwah di Masjid - Maolana, Lutfi; Sobar, Amin; Mahmudah, Mahmudah; Mularsih, Evi Risky (STAI Publisistik Thawalib Jakarta, 2024)
The main objective of this research is to explore the role of Instagram in Masjid Ash-Shomad Tangerang City. It focuses on how Instagram is utilized for socializing mosque activities and religious outreach. The study employs a qualitative approach with field methods. Data from observing the mosque's Instagram account are used to understand the content of religious outreach. The content production process is meticulously documented. Semi-structured interviews are conducted for comprehensive insights. Systematic data analysis involving reduction and triangulation ensures validity. The findings indicate that the use of Instagram by Masjid Ash-Shomad Tangerang City for religious outreach is crucial for socialization and social interaction. The platform disseminates information about religious activities such as worship training, Quran recitation, Islamic arts and culture, and major religious observances. Features like photo posts, videos, and Instastories enable effective communication with congregants and the broader community, conveying relevant religious messages. Instagram also expands the mosque's social network, promotes social activities, and supports distance religious education. However, risks such as negative impacts and the potential lack of direct interaction between preachers and audiences should be mitigated through wise management and attention to ethics. Enhancing open feedback mechanisms is necessary to strengthen relationships with congregants and audiences.